Kebijakan Pembelajaran Daring Ditengah Pandemi Covid-19 Di Sekolah Menengah Atas Negeri 11 di Kabupaten Bone - Andi Amatul Fauziah; Lukman Hakim; Hardianto Hawing (Universitas Muhammadiyah Makassar, 2022)
Referring to the Circular of the Minister of Education and Culture Number 3 of 2020 concerning Prevention of COVID-19 in Education Units, and Number 36962/MPK.A/HK/2020, teaching and learning activities are also carried out online in order to prevent the spread of Corona Virus Disease (COVID-19). . A number of local governments have also closed schools to anticipate the spread of COVID-19. As part of the solution, learning in schools is replaced with learning in the network (online), or familiarly called online. Online learning is a learning system that is not carried out face to face, but uses a platform that can help the teaching and learning process that is carried out even though it is distanced. The purpose of online learning is to provide quality learning services in a massive and open network in order to reach more and wider study space enthusiasts. The implementation of online learning policies in the midst of the Covid-19 pandemic at 11 state high schools in Bone Regency was carried out based on central government regulations and then continued with circulars from the Bone Regency regional government which remained based on policies that had been set by the central government, the implementation of learning Online learning at SMAN 11 Bone Regency is carried out by utilizing several online-based learning platforms or applications, namely Zoom and WhatsAap. Evaluation of Online Learning Policies Amid the Covid-19 Pandemic At State High School 11 In Bone Regency, the school carried out an evaluation so that it could find out the obstacles found during the online learning process and look for solutions related to the obstacles found so that online learning could be carried out properly